In Vitro Diagnostics: Designed Microdevices for In Vitro Diagnostics (Small Methods 10/2017). Issue 10 (16th October 2017) - Sun, Xuming; Wan, Jing jing; Qian, Kun
Abstract : In vitro diagnostics (IVD) refers to in vitro tests of biological specimens and is universally applied in current bioresearch and clinics. In article number1700196, Kun Qian and co‐workers review the principle, design, and application of microdevice‐based IVD with regard to the two major aspects: i) capture and recognition; and ii) detection methods. This provides a guide for the design of new types of microdevice for IVD.